IDENTIFICATION OF FRUIT FLIES AND THEIR ABUNDANCE IN BANDUNG AND TANJUNGPINANG RESIDENTIAL RESIDENTS - Dirga Saputra, Eka
Fruit flies are pests that attack various types of fruit. Different types of fruit flies in Indonesia. Even in one species, fruit flies can have differences from one another. This difference can be seen in terms of morphology such as the pattern on the abdomen shaped like the letter T, wing patterns, etc. This study was conducted to analyze the morphological differences in the abdominal pattern of fruit flies in Bandung and Tanjung Pinang. Collection of fruit flies was carried out using traps of fruit flies modified from the stainer with methyl eugenol attractants. Traps in the form of used bottles of 600 ml volume mineral water which are placed in 20 locations randomly for 2 days. The activity was repeated 3 times. Fruit flies from traps, taken to the laboratory for identification. Samples were photographed and matched with identification books which were further analyzed. Based on the analysis of the abdominal T pattern no morphological differences were found in the abdominal patterns in either place. In both places there are 6 types of Bactrocera dorsalis abdominal patterns, 1 type of Bactrocera carambolae abdominal patterns and 1 type of Bactrocera umbrosa abdominal patterns. In Tanjungpinang more Bactrocera dorsalis are Bactrocera dorsalis type 1, Bactrocera dorsalis type 2 and Bactrocera dorsalis type 6. Whereas in Bandung, more Bactrocera dorsalis is Bactrocera dorsalis type 1 and Bactrocera dorsalis type 4.